The Effect of Rhythmic Breathing Distraction on The Anxiety Level of Preoperative Patients Under General Anesthesia at Wijayakusuma Hospital, Purwokerto - Keisya Nur Azizah; Marta Tania Gabriel Ching Cing; Rully Annisa; Tati Hardiyani (International Journal of Health and Pharmaceutical (IJHP), 2026)
Anxiety is a common psychological condition experienced by patients before undergoing medical procedures, especially surgical procedures, which can affect physiological stability, comfort, and patient readiness to receive the procedure. One non-pharmacological method to reduce anxiety levels is rhythmic breathing distraction, which has the potential to reduce the body's stress hormone levels, such as adrenaline and cortisol, in preoperative patients. This study aimed to analyze the effect of rhythmic breathing distraction on the anxiety levels of preoperative patients under general anesthesia. This study used a pre-experimental method with a one-group pretest-posttest design. The study was conducted at Wijayakusuma Hospital, Purwokerto, from October to November 2025, and included a total of 38 respondents. Data analysis was performed using the Wilcoxon signed-rank test with a significance level of α = 0.05. The results showed a significant decrease in anxiety levels after the rhythmic breathing distraction intervention (p <0.001). The average anxiety score before the intervention was 21.05 and after the intervention was 12.03. It can be concluded that rhythmic breathing distraction significantly influences preoperative anxiety levels in patients undergoing general anesthesia. This non-pharmacological intervention, rhythmic breathing distraction, can be used as an alternative for managing anxiety in preoperative patients.